Proline Metabolism in Tumor Growth and Metastatic Progression - D'Aniello, Cristina; Patriarca, Eduardo J.; Phang, James M.; Minchiotti, Gabriella (Frontiers in Oncology, 2020)
Cancer cells show a formidable capacity to survive under stringent conditions, to elude mechanisms of control, such as apoptosis, and to resist therapy. Cancer cells reprogram their metabolism to support uncontrolled proliferation and metastatic progression. Phenotypic and functional heterogeneity are hallmarks of cancer cells, which endow them with aggressiveness, metastatic capacity, and resistance to therapy. This heterogeneity is regulated by a variety of intrinsic and extrinsic stimuli including those from the tumor microenvironment. Increasing evidence points to a key role for the metabolism of non-essential amino acids in this complex scenario. Here we discuss the impact of proline metabolism in cancer development and progression, with particular emphasis on the enzymes involved in proline synthesis and catabolism, which are linked to pathways of energy, redox, and anaplerosis. In particular, we emphasize how proline availability influences collagen synthesis and maturation and the acquisition of cancer cell plasticity and heterogeneity. Specifically, we propose a model whereby proline availability generates a cycle based on collagen synthesis and degradation, which, in turn, influences the epigenetic landscape and tumor heterogeneity. Therapeutic strategies targeting this metabolic-epigenetic axis hold great promise for the treatment of metastatic cancers.